Efecto del voltaje en el desempeño de las cocinas de inducción - Vela Pilaquinga, Edwin Orlando (2015)
This paper presents the results of an experimental investigation of the effects that voltage variations in the performance of induction cookers to be sold in the country is presented, Initially the basic concepts and principles of operation of induction cooking is presented; as also shown in synthesized form the general characteristics of plan incorporating induction cookers in the homes of the Ecuadorian population, highlighting the most important elements. The experimental research was developed through testing in the laboratory of the Salesian Polytechnic University, for a period of 15 days, in a sample of two induction cookers. Additionally, tests the same that was installed in 3 different residential houses in different parts of the city of Quito were performed with other induction cooker for 3 days. This research work includes the description of the elements used for testing and for the acquisition of data and procedures. The input and output variables were recorded using a power quality analyzer. The test results were analyzed and refined and graphically presented and comparative tables that identify the performance of induction cookers against voltage variations. In the work includes analytical and graphical comparison of the effects of voltage variation in induction cooker sample with those technical literature presents for electric cookers and induction motors Finally conclusions and recommendations